Feeding practices in infants: ritual factors dominating mother’s education - a cross sectional study - Kumar, Dinesh; Sharma, Indra Kumar; Singh, Mukesh Vir; Kumar, Durgesh; Shukla, Krishan Mohan; Singh, Dinesh Kumar (International Journal of Research in Medical Sciences, 2017)
Background: The objective was to know the impact of mother education on feeding practices of infants. Methods: Observational analytic cross sectional study. We used Semi-structured, pre-tested questionnaire to interview 355 mothers of infants, aged one and half to 12 months, who came in OPD of Department of Paediatrics UPRIMS and R, Saifai for immunization or some problem. Results: Total 267 (75.2 %) out of 355 women had initiated breast feeding within 24 hours of birth. 172 (48.5%) mothers exclusively breast fed their infants. Total 166 (46.8%) practiced Prelacteal feed. Out of 166 subjects, 121 (34.1%) practiced for 7 days and 41 (12.7%) beyond the 7 days. There were highly significant relationship found between education level of mothers with type of breast feeding, in the form of exclusive or non- exclusive breast feeding and Prelacteal feeding practices ( p <. 05). Relation between education level of mother with time of initiation of breast feeding since birth was not found statistically significant (p >0.05), but an important pattern of initiation of breast feeding was seen at the different level of mothers education. Conclusion: Ritual and customary factors have much impact then mother’s education on breast feeding practices of infants. Apart from education, breast feeding awareness programme should be increased including both literate and illiterate mothers.